The effects of turbulence on three‐dimensional magnetic reconnection at the magnetopause - L. Price; M. Swisdak; J. F. Drake; P. A. Cassak; J. T. Dahlin; R. E. Ergun (Geophysical Research Letters)
Abstract Two‐ and three‐dimensional particle‐in‐cell simulations of a recent encounter of the Magnetospheric Multiscale Mission (MMS) with an electron diffusion region at the magnetopause are presented. While the two‐dimensional simulation is laminar, turbulence develops at both the X line and along the magnetic separatrices in the three‐dimensional simulation. The turbulence is strong enough to make the magnetic field around the reconnection island chaotic and produces both anomalous resistivity and anomalous viscosity. Each contribute significantly to breaking the frozen‐in condition in the electron diffusion region. A surprise is that the crescent‐shaped features in velocity space seen both in MMS observations and in two‐dimensional simulations survive, even in the turbulent environment of the three‐dimensional system. This suggests that MMS's measurements of crescent distributions do not exclude the possibility that turbulence plays an important role in magnetopause reconnection.